Collaborative Network for Developing the Potential of Children with Disabilities in Special Education Centers in the Northeastern Region - Aksorn, Katawoot; Thawinkarn, Dawruwan; Ketchatturat, Jatuphum (Journal of Neonatal Surgery, 2025)
This study aims to 1) Examine the consistency and alignment of the indicator model for collaborative networks in enhancing the potential of children with disabilities in special education centers with empirical data. 2) Investigate the characteristics of collaborative networks in developing the potential of children with disabilities, the conditions influencing their formation, the strategies employed, and the resulting outcomes within special education centers. The research sample consisted of 360 administrators and teachers from special education centers in the Northeastern region of Thailand, selected through a multi-stage random sampling method. Data collection was conducted using a five-point Likert scale questionnaire. The data were analyzed using basic statistical methods, confirmatory factor analysis (CFA), and theoretical analysis based on a grounded theory approach. Findings The collaborative network for developing the potential of children with disabilities in special education centers in the Northeastern region comprises four key components. 1.Interdisciplinary professional learning 2.Resource sharing 3.Mutual trust among network members, and 4.shared goals and values in developing the potential of children with disabilities. The model fit analysis confirmed the alignment between the indicator model and empirical data, with the following statistical values: χ² = 347.541, df = 306, χ²/df = 1.1358, P-Value = 0.0501, RMSEA = 0.019, SRMR = 0.029, CFI = 0.993, and TLI = 0.991. Furthermore, the study explored the characteristics of the collaborative network, the conditions influencing its formation, the strategies employed, and its consequential outcomes. The results indicate that the collaborative network conforms to the four identified components. Additionally, four key strategies were identified, shaped by two contextual conditions and two intervening conditions. The outcomes of these networks were observed across three domains 1.The development of special education centers, 2.The professional growth of administrators, teachers, and personnel, and 3.The strengthening of collaborative networks.